2016
DOI: 10.1074/jbc.m116.718353
|View full text |Cite
|
Sign up to set email alerts
|

PilN Binding Modulates the Structure and Binding Partners of the Pseudomonas aeruginosa Type IVa Pilus Protein PilM

Abstract: Pseudomonas aeruginosa is an opportunistic bacterial pathogen that expresses type IVa pili. The pilus assembly system, which promotes surface-associated twitching motility and virulence, is composed of inner and outer membrane subcomplexes, connected by an alignment subcomplex composed of PilMNOP. PilM binds to the N terminus of PilN, and we hypothesize that this interaction causes functionally significant structural changes in PilM. To characterize this interaction, we determined the crystal structures of Pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 71 publications
9
50
1
2
Order By: Relevance
“…PilG is likely to become a stable part of the machinery once PilM has been recruited to the PilNOP complex (PilG does not form a stable complex with PilNOP), which is consistent with Tfp subtomograms showing that the PilG "dome" structure requires the presence of the PilM ring (34). Similarly, the ATPase PilF is likely to be recruited to the complex via interactions with PilM (PilF does not copurify with PilNOP) (33,43) and/or PilG (32), which is consistent with Tfp subtomograms where the PilF "disc" requires both the PilM ring and PilG dome (34). Finally, PilE from a pool of processed subunits awaiting in the membrane would diffuse to the PilFGMNOP complex (28), which would scoop them out of the lipid bilayer and into the base of a growing filament (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…PilG is likely to become a stable part of the machinery once PilM has been recruited to the PilNOP complex (PilG does not form a stable complex with PilNOP), which is consistent with Tfp subtomograms showing that the PilG "dome" structure requires the presence of the PilM ring (34). Similarly, the ATPase PilF is likely to be recruited to the complex via interactions with PilM (PilF does not copurify with PilNOP) (33,43) and/or PilG (32), which is consistent with Tfp subtomograms where the PilF "disc" requires both the PilM ring and PilG dome (34). Finally, PilE from a pool of processed subunits awaiting in the membrane would diffuse to the PilFGMNOP complex (28), which would scoop them out of the lipid bilayer and into the base of a growing filament (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…but there is ample evidence that they establish multiple binary/ ternary interactions at the cytoplasmic membrane (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Moreover, in a recent study in Myxococcus xanthus, in which the entire Tfp machinery was visualized by cryoelectron tomography (34), it was shown that these five proteins form a series of interconnected layers spanning the cytoplasmic membrane, which is a priori compatible with a role in filament assembly.…”
Section: Significancementioning
confidence: 99%
“…In our work, only PilM or PilP could modulate the PilNO core interface. We speculate that subtle reorientation of PilN and PilO may occur during the transition between resting and active or "extension" versus "retraction" states of the T4P system, consistent with the hypothesis that PilM may disengage from PilN (41). Although a ratcheting-type mechanism, in which PilNO conformational dynamics might contribute to the stepwise addition or removal of pilin subunits cannot yet be ruled out, our data do not support this idea.…”
Section: Piln and Pilo Homodimers May Represent A Functional Rather Tcontrasting
confidence: 52%
“…6, B and C), suggesting that the PilNO interface no longer adopts an orientation permissive for disulfide bond formation. New crystal structures of a P. aeruginosa PilM homodimer and of monomeric PilM fused to part of its binding partner, PilN (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), revealed that in the absence of PilN, the seven N-terminal residues of PilM (PilM (1-7)) bind in the PilN binding cleft of a second PilM monomer (41). Thus, PilM dimerizes in the absence of PilN.…”
Section: Piln and Pilo Homodimers May Represent A Functional Rather Tmentioning
confidence: 99%
“…In the model bacterium Pseudomonas aeruginosa, an inner membrane motor subcomplex consisting of the platform protein PilC and three hexameric ATPases-PilB, PilT, and PilU-provide energy for T4aP extension and retraction (7)(8)(9). A second inner membrane alignment subcomplex composed of PilMNOP connects the motor subcomplex with an outer membrane secretin composed of multimeric PilQ (2,(10)(11)(12)(13). Finally, the pilus fiber is composed of the major pilus subunit PilA and a set of minor pilins that prime pilus assembly and export the adhesin PilY1 to the cell surface (14).…”
mentioning
confidence: 99%